2005
DOI: 10.1158/1078-0432.ccr-05-0646
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Vascular Endothelial Growth Factor C in Papillary Thyroid Carcinoma Correlates with Cervical Lymph Node Metastases

Abstract: Purpose: Despite recent studies showing that vascular endothelial growth factor C (VEGF-C) mRNA is up-regulated in papillary thyroid carcinoma (PTC), the role of VEGF-C in lymph node metastasis is still unclear. The aim of this study is to investigate the expression pattern of VEGF-C immunoreactive protein in PTC and its relationship with cervical lymph node metastasis. Experimental Design: Tissue samples were obtained from 39 specimens of PTC (20 with and 19 without lymph node metastasis) as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 35 publications
7
64
2
1
Order By: Relevance
“…22 VEGF is highly expressed in many human cancers. 23 Its expression is positively related to angiogenesis. The tumor sections of nude mice displayed significant carcinoma necrosis in the tumor masses (visible by both naked-eye observation and immunochemistry detection), which corresponded to the decreased expression of VEGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 VEGF is highly expressed in many human cancers. 23 Its expression is positively related to angiogenesis. The tumor sections of nude mice displayed significant carcinoma necrosis in the tumor masses (visible by both naked-eye observation and immunochemistry detection), which corresponded to the decreased expression of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…The protein expression of vascular endothelial growth factor (VEGF), which served as a marker of angiogenesis, was measured by immunohistochemistry using a VEGF antibody (Santa Cruz, Santa Cruz, CA). 17 Statistics and data analysis All the experiments were performed in triplicate except the animal experiment (n ¼ 5). All of the data are expressed as mean ± s.d.…”
mentioning
confidence: 99%
“…Increased serum concentrations of VEGF-A and EGFR protein were also reported in PTC (36,39), eventually inducing systemic effects. It is interesting to note that increased levels were especially linked with PTC characterized by lymph node metastases and more aggressive behavior (40) and patients over the age of 45 (41). Again, post-Chernobyl PTC appeared more aggressive at presentation with lymph node metastasis (60-80%); other extrathyroidal spread and venous invasion were commonly observed (11)(12)(13).…”
Section: Figmentioning
confidence: 98%
“…Studies have demonstrated that VEGFR is overexpressed in thyroid cancer (41) and VEGF-C immunoreactive protein is correlated with papillary lymph node metastases (42). Serum VEGF is significantly elevated in patients with papillary thyroid cancer compared with the control group (43), especially in patients with metastatic differentiated thyroid cancer but not in those with poorly differentiated thyroid cancer metastases (44).…”
Section: Vegf Receptormentioning
confidence: 99%